Low-cost gel-filled microwell array device for screening marine microbial consortium - Duran, Clelia; Zhang, Shiyi; Yang, Chongyang; Falco, Maria Lorena; Cravo-Laureau, Cristiana; Suzuki-Minakuchi, Chiho; Nojiri, Hideaki; Duran, Robert; Sassa, Fumihiro (Frontiers in Microbiology, 2022)
In order to exploit the microbes present in the environment for their beneficial resources, effective selection and isolation of microbes from environmental samples is essential. In this study, we fabricated a gel-filled microwell array device using resin for microbial culture. The device has an integrated sealing mechanism that enables high-density isolation based on the culture of microorganisms; the device is easily manageable, facilitating observation using bright-field microscopy. This low-cost device made from PMMA (polymethyl methacrylate)/PET (polyethylene terephthalate) has 900 microwells (600 μm× 600 μm× 350 μm) filled with microbial culture gel medium in glass slide-sized plates. It also has grooves for maintaining the moisture content in the micro-gel. The partition wall between the wells has a highly hydrophobic coating to inhibit microbial migration for neighboring well and to prevent exchange of liquid substances. After being hermetically sealed, the device can maintain moisture in the agarose gels for 7 days. In the bacterial culture experiment using this device, the bacteria from marine microbial sample could be isolated and cultured in individual wells after 3 days. Moreover, the isolated bacteria could be picked up from wells and re-cultured. This device is effective for the first screening of microorganisms from marine environmental samples.